2023
DOI: 10.7554/elife.83484
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical supervisors’ role modeling of open science practices

Abstract: Supervision is one important way to socialize Ph.D. candidates into open and responsible research. We hypothesized that one should be more likely to identify open science practices (here publishing open access and sharing data) in empirical publications that were part of a Ph.D. thesis when the Ph.D. candidates’ supervisors engaged in these practices compared to those whose supervisors did not or less often did. Departing from thesis repositories at four Dutch University Medical centers, we included 211 pairs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Third, extraction was performed by two raters in cases of doubt. The high reliability of the outcome is supported not just by the high IRR, but also by two further observations: First, in the meta-research study by Haven et al [ 35 ], manual confirmation of open data status substantially increased the correlation between the open data status ascribed to supervisor and supervisee articles. Second, we observe only a low one-digit number of open data articles which we missed in the screening, according to the post-hoc registration available to Charité researchers.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Third, extraction was performed by two raters in cases of doubt. The high reliability of the outcome is supported not just by the high IRR, but also by two further observations: First, in the meta-research study by Haven et al [ 35 ], manual confirmation of open data status substantially increased the correlation between the open data status ascribed to supervisor and supervisee articles. Second, we observe only a low one-digit number of open data articles which we missed in the screening, according to the post-hoc registration available to Charité researchers.…”
Section: Discussionmentioning
confidence: 92%
“…In an independent analysis, Haven et al [ 35 ] screened a subset of 2042 articles published by biomedical researchers at four university medical centers (UMCs) in the Netherlands. They found that out of these articles, there were 179 articles with shared datasets detected by ODDPub, and 191 datasets were manually checked in Numbat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this must not only be in the context of institutional incentivization. The results by Haven et al [35] show a strong effect of manual screening.…”
Section: Scope and Applicabilitymentioning
confidence: 92%